Vertical Transmission of Hepatitis E Virus Infection Among Antenatal Attendees in Ekiti, Nigeria: A Longitudinal Cohort Study - Adebayo A. Adeniyi*1, Kolawole A. Fasakin*2, Mathew O. Adebisi 3, Olufunke B. Bolaji 4, Olumide M. Ayankunle 5, Musah Yusuf 6, Oluwaserimi A. Ajetunmobi 7, Abiodun I. Okunlola 8, Olumide E. Adewara9, Babatunde S. Awoyinka 10, Adewumi Bakare 11, Adeshola A (Sokoto Journal of Medical Laboratory Science)
Hepatitis E virus (HEV) infection in pregnancy is a serious health issue associated with spontaneous miscarriage, preterm labour and also accounts for 30% maternal mortality in the third trimester. This study was carried out to determine the anti-HEV prevalence, HEV vertical transmission and possible pregnancy complications among the antenatal attendees attending the two tertiary facilities in Ekiti State. This longitudinal cohort study involved 300 antenatal attendees recruited over a period of 15 months. Plasma samples were initially screened for anti-HEV antibodies using rapid enzyme immunoassay followed by ELISA assay as the gold standard. Seropositive mothers were followed up till delivery. Pregnancy complications and vertical transmission were reported. Descriptive statistics was used to obtain frequency, percentages, mean and standard deviation using SPSS software version 21 software for data analyses. Correlation between viral prevalence age was also tested and a p-value of < 05 was considered statistically significant. Performance characteristics of the rapid immunochromatographic technique was evaluated. The HEV seroprevalence of 2.0% was recorded among the antenatal attendees with vertical transmission rate of 16.7%. The sensitivity and negative predictive values of rapid kit for both HEV-IgM and HEV-IgG antibodies were 100%, the specificity was 90% for HEV-IgG and 99.7% for HEV-IgM. Study also showed that 25.67%, 14% and 6.0% of the participants respectively had abortion, preterm deliveries and postpartum complications. HEV infection still remains a significant public health burden in view of its contribution to maternal and neonatal morbidity and mortality especially in the third trimester. Vertical transmission of HEV is still a challenge and inculcation of routine screening for HEV antibodies into antenatal care protocol will help to identify at risk mothers and reduce pregnancy complications.